Generation of Power-Exponent-Phase Vortex Beam Arrays Based on All-Dielectric Metasurfaces - Jiale Guo; Chuan Shen; Jinkun Hu; Yong Zhou; Cheng Zhang; Sui Wei (IEEE Photonics Journal, 2024)
Optical vortices (OV) with an open shape have a unique function in directional particle transport and collection. A power-exponent-phase vortex (PEPV) has received particular attention as a type of unconventional vortex beam with a large opening and carrying orbital angular momentum (OAM). So far, only the generation methods and properties of an individual PEPV beam have been studied and analyzed. In this paper, we use dielectric metasurfaces instead of the conventional bulky optical device to generate PEPV arrays with a uniform diffracted intensity distribution and a controllable correlation between the topological charge number and the diffraction order. This approach is based on the theory of PEPV and combined with the principle of Dammann grating. The proposed method provides a new platform for various applications of light-matter interactions such as optical communication, optical encryption, and multi-particle manipulation.